PENGARUH SOSIALISASI PROGRAM WAJIB BELAJAR PENDIDIKAN DASAR SEMBILAN TAHUN TERHADAP PARTISIPASI MASYARAKAT DALAM BIDANG PENDIDIKAN DI KELURAHAN ARGASUNYA KECAMATAN HARJAMUKTI KOTA CIREBON - Dini Widiyana; Mukarto Siswoyo; Farida Nurfalah (Jurnal Ilmiah Publika, 2020)
Research by the author is the Effect of Socialization Compulsory Nine- Year Basic Education Against Public Participation in the Field of Education in Sub Argasunya Harjamukti District of Cirebon. The problem that the writer suggested was the participation of society, especially in the field of education in Sub Argasunya Harjamukti District of Cirebon not maximized, the problem allegedly caused by the non-optimal implementation of the socialization program of compulsory nine-year education by the Cirebon City Department of Education. The research method that I use is a survey method, with quantitative descriptive analysis techniques. The research question asked, is there any influence of socialization program compulsory nine-year education on community participation in village Argasunya Harjamukti District of Cirebon. In the research showed that the result of socialization conducted by the Department of Education of City of Cirebon is quite good, but not optimal, as seen from the success of socialization which reached 65.6% with a total score of 3938, and community participation in education is quite good but not optimal as it reached 64.2% with a total score of 3854. the implementation of the program socialization compulsory nine-year education has a fairly close correlation to the participation in the Village Argasunya Harjamukti District of Cirebon to the value ryx count 0,645 and 0,000 is a significant value less than 0.05 (0.000 <0.05). Because of the significant value less than 0.05 then there is a positive and significant influence between the socialization of education programs on community participation in education. Thus H0 (the null hypothesis) is rejected and Ha (Alternative Hypothesis) is received.Keywords: Socialization, Compulsory, Public Participation.